Optimization of Aspergillus fijiensis β-fructofuranosidase expression and production using Pichia pastoris, for the production of fructooligosaccharides from sucrose - Coetzee, Gerhardt (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.